Consensus design of a calibration experiment for human fear conditioning. (May 2023) - Bach, Dominik R.; Sporrer, Juliana; Abend, Rany; Beckers, Tom; Dunsmoor, Joseph E.; Fullana, Miquel A.; Gamer, Matthias; Gee, Dylan G.; Hamm, Alfons; Hartley, Catherine A.; Herringa, Ryan J.; Jovanovic, Tanja; et al.
Abstract: Fear conditioning is a widely used laboratory model to investigate learning, memory, and psychopathology across species. The quantification of learning in this paradigm is heterogeneous in humans and psychometric properties of different quantification methods can be difficult to establish. To overcome this obstacle, calibration is a standard metrological procedure in which well-defined values of a latent variable are generated in an established experimental paradigm. These intended values then serve as validity criterion to rank methods. Here, we develop a calibration protocol for human fear conditioning. Based on a literature review, series of workshops, and survey of N = 96 experts, we propose a calibration experiment and settings for 25 design variables to calibrate the measurement of fear conditioning. Design variables were chosen to be as theory-free as possible and allow wide applicability in different experimental contexts. Besides establishing a specific calibration procedure, the general calibration process we outline may serve as a blueprint for calibration efforts in other subfields of behavioral neuroscience that need measurement refinement. Highlights: Heterogeneity in human fear conditioning readouts limits comparability of results. We report a multi-laboratory consensus on evaluation of readouts. Literature review identifies crucial design elements for calibration experiments. 25 design elements are formulated based on expert survey. Generic consensus process is translatable to other disciplines.